2021
DOI: 10.1080/17518253.2021.1939435
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory role of synthesized Nickel oxide nanoparticles against Hep-G2, MCF-7, and HT-29 cell lines: the inhibitory role of NiO NPs against Hep-G2, MCF-7, and HT-29 cell lines

Abstract: Nickel oxide nanoparticles (NiO NPs) were synthesized via the facile sol-gel method. The synthesized NiO NPs were characterized using X-ray diffraction (XRD), Field-Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM), Raman and Fourier Transform Infrared (FT-IR) techniques. The effect of particle size was analyzed on structural alterations, electrochemical behaviors, and cytotoxic effect of synthesized NiO NPs. According to TEM results, the particle sizes of synthesized NiO NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In catalyst NiBOx-1000, B atoms formed planar BO 3 structures with three oxygen atoms, while Ni atoms formed octahedral structures with six O atoms within the crystal lattice of Ni 3 (BO 3 ) 2 ( Figure 2 b and Figure S7 ). These observations were validated by FTIR spectra, which exhibited prominent Ni-O vibrations [ 23 ] between 600–723 cm −1 and BO 3 bond vibrations between 1200–1500 cm −1 [ 14 , 24 ], and a distinct peak at 723 cm −1 corresponded to -OH vibrations ( Figure 2 e, red). The structural diagram of AlBOx-1000 revealed two distinct forms of Al atoms: one formed an octahedral structure with six oxygen atoms, while the other exhibited five-coordinated structures with five oxygen atoms ( Figure 2 c and Figure S8 ).…”
Section: Resultsmentioning
confidence: 61%
“…In catalyst NiBOx-1000, B atoms formed planar BO 3 structures with three oxygen atoms, while Ni atoms formed octahedral structures with six O atoms within the crystal lattice of Ni 3 (BO 3 ) 2 ( Figure 2 b and Figure S7 ). These observations were validated by FTIR spectra, which exhibited prominent Ni-O vibrations [ 23 ] between 600–723 cm −1 and BO 3 bond vibrations between 1200–1500 cm −1 [ 14 , 24 ], and a distinct peak at 723 cm −1 corresponded to -OH vibrations ( Figure 2 e, red). The structural diagram of AlBOx-1000 revealed two distinct forms of Al atoms: one formed an octahedral structure with six oxygen atoms, while the other exhibited five-coordinated structures with five oxygen atoms ( Figure 2 c and Figure S8 ).…”
Section: Resultsmentioning
confidence: 61%
“…In another study of NiO NPs obtained from Calotropis gigantea (a crown flower), it was reported that the NPs had significant anticancer effects on the liver cancer (HepG2) cell line 44 . In the study of NiO NPs obtained by a different method, it was stated that NiO NPs could be effective anticancer agents for three different cancer cell lines 46 …”
Section: Resultsmentioning
confidence: 99%
“…44 In the study of NiO NPs obtained by a different method, it was stated that NiO NPs could be effective anticancer agents for three different cancer cell lines. 46…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…The cytotoxicity of Z, ZL, ZS, and ZLS was evaluated against two cell lines: MCF-7 and HT29 (see Figure 7). The former is a representative cellular model used to explore the potential use of nanostructures against breast cancer [39], which is the most common cancer diagnosed among women worldwide, and the fifth most common cause of cancer-related deaths in the last few years [40]. Similarly, the latter is utilized to investigate the possible use of nanomaterials to develop therapies against colorectal cancer [41], which is a complex type of cancer that has remained as the third most common type of cancer diagnosed for men and women worldwide and the third most common cause of cancer-related deaths in the United States of America (USA) [42].…”
Section: Cytotoxic Activity and Ros Assaymentioning
confidence: 99%